Femtosecond time-resolved photoelectron spectroscopy of the benzyl radical. Issue 19 (28th April 2017) - Röder, A.; Humeniuk, A.; Giegerich, J.; Fischer, I.; Poisson, L.; Mitrić, R.
Abstract : We present a joint experimental and computational study of the nonradiative deactivation of the benzyl radical, C7 H7, after UV excitation. Abstract : We present a joint experimental and computational study of the nonradiative deactivation of the benzyl radical, C7 H7, after UV excitation. Femtosecond time-resolved photoelectron imaging was applied to investigate the photodynamics of the radical. The experiments were accompanied by excited state dynamics simulations using surface hopping. Benzyl has been excited at 265 nm into the D-band (ππ*) and the dynamics was probed using probe wavelengths of 398 nm or 798 nm. At a probe wavelength of 398 nm a single time constant of around 70–80 fs was observed. When the dynamics was probed at 798 nm, a second time constant τ 2 = 1.5 ps was visible, which can be attributed to further non-radiative deactivation to the lower-lying D1 /D2 states.